Strategies for building multicultural competence in mental health and educational settings - Constantine, Madonna G.; Sue, Derald Wing (Wiley, 2005)
"Edited and written by renowned multicultural experts, this informative guide is full of concrete strategies and case examples, all geared toward achieving the goal of culturally competent practice. Chapter by chapter, it uses a variety of practice modalities in various settings to help all mental health professionals increase their familiarity and compliance with the APA Multicultural Guidelines." "This timely reference also considers building multicultural competence around indigenous healing practices; in clinical supervision contexts; and in culturally sensitive research. Taken together, the book is a much-needed blueprint for making culturally informed decisions, explaining how the multicultural initiatives you implement today can help shape the field's future."--Jacket.